Natural Disasters in Bangladesh: Impact Analysis Through Input-Output Model - Haque, Afsana; Jahan, Sarwar (Journal of Bangladesh Institute of Planners, 2018)
Flood, cyclone and storm surge, tornado, drought, river bank erosion are common natural hazards in Bangladesh. These hazards strike Bangladesh in regular interval and claim millions of lives, damage properties/assets and infrastructures, influence societal and daily life of people. The disaster caused by each hazard can be classified into direct damages, first-order losses and higher-order/induced losses. In Bangladesh disaster impact assessment are mainly confined with the estimation of direct damages and sometimes with the first-order losses. Assessment of induced losses are almost absent in the disaster related studies for Bangladesh. We argue that assessment of induced losses are necessary to determine individual and community vulnerability, and optimum level of disaster preparedness, mitigation and recovery. This paper demonstrates how InputOutput framework can be employed to analyze higher-order disaster impacts for Bangladesh. JBIP, Vol. 11, 2018 (Printed in June 2020), pp. 11-19